2004
DOI: 10.1038/sj.onc.1207478
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 inhibition of T-cell proliferation is related to prolonged T-cell survival

Abstract: Bcl-2 promotes oncogenesis by inhibiting cell death. Bcl-2 also inhibits proliferation and suppresses tumorigenesis in some settings. To clarify the role of the antiproliferative function of Bcl-2, mice expressing a mutant form of Bcl-2 reported to lack antiproliferative activity were generated (tyrosine 28 to alanine, Bcl-2-Y28A). As expected, both wild type (WT) and Bcl-2-Y28A inhibited apoptosis similarly. In contrast to previous results in cell lines, Bcl-2-Y28A inhibited T-cell proliferation identical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 40 publications
6
54
0
Order By: Relevance
“…Importantly, the Bcl-2 high phenotype is highly correlative with both enhanced rate of survival and mitogen responsiveness of T cells, regardless of their differentiation stage. Numerous studies have shown that Bcl-2 has antiapoptotic effects; however, high levels of Bcl-2 also correlated with decreased proliferation, when using Bcl-2 overexpressing transgenic mice (36). In this study, we observed that actively dividing cells expressed high amounts of the Bcl-2 protein (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Importantly, the Bcl-2 high phenotype is highly correlative with both enhanced rate of survival and mitogen responsiveness of T cells, regardless of their differentiation stage. Numerous studies have shown that Bcl-2 has antiapoptotic effects; however, high levels of Bcl-2 also correlated with decreased proliferation, when using Bcl-2 overexpressing transgenic mice (36). In this study, we observed that actively dividing cells expressed high amounts of the Bcl-2 protein (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…In mouse, forced expression of Bcl-2 delays activation-induced T cells (22,23), whereas Bcl-2 deficiency hastens (22) cell-cycle entry of T cells. The antiproliferative action of Bcl-2 is believed to act by elevating the expression of the negative cell-cycle regulator p27 and retarding S-phase entry (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Due to shared protein functions in apoptosis and proliferation of BCL-2 family proteins is seems that the function in the liver is likely to be related to compensatory proliferation. 22,23 Previous studies in globally deficient BID mice, or in mice with Bcl-2 overexpression, showed impairment in cell proliferation. 21,24,25 However, global Bid deficiency by itself can lead to an increased incidence of chronic myelomonocytic leukemia in aged mice and similar to this, Bad deficiency has been reported to promote the development of lymphoid tumors either spontaneously or in response to sublethal radiation.…”
Section: Discussionmentioning
confidence: 99%